Long term follow-up of multidrug resistant tuberculosis in a pubertal child - Andri Kurnia Wahyudhi; Retno Asih Setyoningrum; Ahmad Suryawan (Indonesian Pediatric Society, 2018)
Increasing awareness of the rising global rates of multidrug-resistant tuberculosis (MDR-TB) has led to a concerted international effort to confront this disease. Nonetheless, despite cure rates >80% in some programs, MDR-TB patients tend to have chronic disease and require prolonged therapy.1-3 Little is known about the long-term results and follow-up of patients with MDR-TB, include the recurrence rate and chronic disability in patients who have recovered from TB.4 There are many side effects and adverse reactions to drugs can occur during MDR-TB treatment. These could be physical and or psychological, as well as reversible or irreversible. Treatment of MDR-TB requires a combination regimen, consists of second and third-line anti-tuberculosis drugs which more toxic than first-line drugs. Additionally, MDR-TB treatment requires a long duration of treatment (18-24 months) and causes discomfort in the patient.5 In a cohort of 60 patients treated for MDR-TB, the most common side effects included gastritis (100%), dermatological disorders (43%), and peripheral neuropathy (16.7).6 While in a cohort of 75 patients, the incidence of depression, anxiety, and psychosis for MDR-TB treatments was 13.3%, 12.0%, and 12.0%, respectively.7 Aggressive and effective management are needed so the patient can tolerate the treatment and remain adhere the treatment.8 Long-term follow-up is required for the rehabilitation of disorders due to psychosocial sequelae. As such, psychosocial support can be benefit pediatric MDR-TB patients. Here, we present a case report on a two-year follow-up of a pubertal child with MDR-TB, focusing on medical aspects and her development.